2007
DOI: 10.3727/000000007783464777
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endothelial Progenitor Cells in Ischemic Cerebral and Heart Diseases

Abstract: Ischemic heart and cerebral diseases are complex clinical syndromes. Endothelial dysfunction caused by dysfunctional endothelial progenitor cells (EPCs) is thought to play a major role in pathophysiology of both types of disease. Healthy EPCs may be able to replace the dysfunctional endothelium through endogenous repair mechanisms. EPC levels are changed in patients with ischemic cerebrovascular and cardiovascular disease and EPCs may play a role in the pathophysiology of these diseases. EPCs are also a marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 118 publications
0
35
0
Order By: Relevance
“…Although cell therapy has been proven to be effective in improving ischemia-related organ dysfunction [7,8,24,25], the benefit of cell therapy on PAH has not been fully elucidated. Some recent studies reveal that EPC therapy notably reduces MCT-induced rat PAH [10][11][12].…”
Section: Timing and Role Of Bmdepcs On Pahmentioning
confidence: 98%
“…Although cell therapy has been proven to be effective in improving ischemia-related organ dysfunction [7,8,24,25], the benefit of cell therapy on PAH has not been fully elucidated. Some recent studies reveal that EPC therapy notably reduces MCT-induced rat PAH [10][11][12].…”
Section: Timing and Role Of Bmdepcs On Pahmentioning
confidence: 98%
“…EPC population is most commonly characterized through expression of CD34, CD133, and kinase domain receptor (KDR) [79][80][81]. Some studies have suggested that patients with PH had reduced peripheral EPCs [82][83][84][85][86]; however, the relationship between the number of peripheral EPCs and PH remains controversial [87][88][89][90]. EPCs derived from hypoxia-derived PH mice were found to have altered functions such as decreased migratory response to stromal cell-derived factor-1a (SDF-1a), adhesion to fibronectin, and incorporation into the vascular network [88].…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%
“…In 2010, women showed significantly higher mortality rates than men, and non-Hispanic blacks showed significantly higher mortality rates than non-Hispanic whites. Aged population cohorts (75)(76)(77)(78)(79)(80)(81)(82)(83)(84) and C85 years of age) show the highest PH mortality (47.9/100,000 and 108.7/100,000, respectively, 2010 data) [3]. Mechanisms for the development of PH are complex and may be idiopathic, genetic, or secondary to left heart disease, lung diseases, and/or chronic thromboembolism.…”
Section: Introductionmentioning
confidence: 97%
“…Mobilized endothelial progenitor cells (EPCs) contribute to postnatal neovascularization, reendothelialization, and angiogenesis via paracrine actions. 10,11 The CD34 -group includes the mesenchymal stem cells (MSCs). A synopsis of the current thinking on the potential value of each cell type in cardiac repair/ regeneration follows (Table I).…”
Section: Bone Marrow-derived Stem Cellsmentioning
confidence: 99%
“…A hurdle that needs to be overcome to make clinical use of EPCs practical in heart treatments is their low circulating numbers, which is further reduced by atherosclerosis and age. 1,8,11 As previously discussed, 1 molecular strategies represent a logical approach to improve the number, mobilization, homing, and survivability/engraftment of autologous EPCs in the injured heart. In vitro, expansion of EPCs in culture is a complementary strategy that is also being undertaken.…”
mentioning
confidence: 99%